2014
DOI: 10.1093/brain/awu078
|View full text |Cite
|
Sign up to set email alerts
|

Chasing central nervous system plasticity: the brainstem’s contribution to locomotor recovery in rats with spinal cord injury

Abstract: Anatomical plasticity such as fibre growth and the formation of new connections in the cortex and spinal cord is one known mechanism mediating functional recovery after damage to the central nervous system. Little is known about anatomical plasticity in the brainstem, which contains key locomotor regions. We compared changes of the spinal projection pattern of the major descending systems following a cervical unilateral spinal cord hemisection in adult rats. As in humans (Brown-Séquard syndrome), this type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(124 citation statements)
references
References 55 publications
5
113
2
Order By: Relevance
“…The number of ME-positive cells was analyzed by unbiased stereological analysis on every fourth coronal brainstem section using a fluorescence microscope (10ϫ, Axioskop 2, Zeiss). Brain sections were fitted into an atlas-based (Paxinos and Watson, 2009, RRID:nlx_152120) template using defined and prominent anatomical landmarks (facial nerve 7N, inferior olive and pyramidal decussation) (for detailed description, see Zörner et al, 2014), thereby normalizing the analysis to potential tissue atrophy. Retrogradely labeled cells were quantified in four regions of the reticular column: the pontine reticular nucleus, oral part (PnO), the pontine reticular nucleus, caudal part (PnC), the NRG, and the medullary reticular nucleus, ventral part (MdV).…”
Section: Quantification Of Neuroanatomical Tracingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of ME-positive cells was analyzed by unbiased stereological analysis on every fourth coronal brainstem section using a fluorescence microscope (10ϫ, Axioskop 2, Zeiss). Brain sections were fitted into an atlas-based (Paxinos and Watson, 2009, RRID:nlx_152120) template using defined and prominent anatomical landmarks (facial nerve 7N, inferior olive and pyramidal decussation) (for detailed description, see Zörner et al, 2014), thereby normalizing the analysis to potential tissue atrophy. Retrogradely labeled cells were quantified in four regions of the reticular column: the pontine reticular nucleus, oral part (PnO), the pontine reticular nucleus, caudal part (PnC), the NRG, and the medullary reticular nucleus, ventral part (MdV).…”
Section: Quantification Of Neuroanatomical Tracingsmentioning
confidence: 99%
“…Compensatory sprouting of spared descending systems was associated with functional recovery after unilateral hemilesions (Rosenzweig et al, 2010). Interestingly, Zörner et al (2014) showed that restricted electrolytic microlesion of the ipsilesional NRG resulted in the reappearance of significant deficits of forelimb and hindlimb locomotion in chronic C4 hemisected rats. The recovered weight support of the ipsilesional forelimb as well as the improved hindpaw clearance and step width seen at 4 months after SCI significantly worsened 2 d after ipsilesional NRG ablation.…”
Section: Recovery Of Locomotor Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…skilled motor function) (Lemon, 2008), while the dorsal column nuclei and medial lemniscus (Liao et al, 2015) and the periaqueductal grey (PAG) (Benarroch, 2012) are involved in sensory processing and pain modulation. Crucially, structural reorganization of brainstem pathways and nuclei has been associated with functional recovery following experimental SCI (Zaaimi et al, 2012, Zörner et al, 2014). Thus, understanding trauma-induced pathophysiological processes affecting the brainstem pathways and nuclei might offer crucial insights into neurodegeneration and plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the CST is not the only descending tract that affects movement and is not be the only projection system that conveys functional recovery (Han et al, 2013; Hurd, Weishaupt & Fouad, 2013). Spared reticulospinal fibers play an important role in the recovery process through spontaneous compensatory sprouting and increases in density after injury; they may also operate caudal to the lesion by enhancing indirect access to reticulospinal commands (Ballermann & Fouad, 2006; Zorner et al, 2014). Therefore, we hypothesize that the nerve fiber circuit underlying repair in this study was composed of CST and reticulospinal fibers and propriospinal neurons.…”
Section: Discussionmentioning
confidence: 99%